Oxidative Stress Status in Heat Shock Sheep Controlled Shearing and Ascorbyl Palmitate Administration - Taofik, Ahmad; Yusuf, Muhammad (Jurnal Peternakan, 2024)
Indonesia has very hot temperatures and high humidity, making it unfavorable for sheep whose covered with thick fur. Shearing enlarges and accelerates heat dissipation from the sheep's body, giving antioxidants that help reduce the negative effects of excessive free radical production.  Ascorbic acid is an antioxidant but is easily decomposed when it enters the digestive system of ruminants. Ascorbyl palmitate (AP) is ascorbic acid in the form of an ester which is insoluble in water. The aim of this study was to analyze the effect of shearing and administration of AP antioxidants on oxidative stress conditions in Padjadjaran sheep subjected to heat shock.   The shaving treatment consisted of not shaving (s0) and shearing (s1),and the treatment of giving the antioxidant ascorbyl palmitate consisted of not being given (a0) and being given (a1).  Sheep were subjected to shearing, their hair was trimmed until ± 10 mm in length was left, and sheep as object of study were treated with ascorbyl palmitate at a dose of 400 mg head-1 day-1. The combination treatment was not shaved – not given the antioxidant ascorbyl palmitate (s0a0), only shaved (s1a0), only given the antioxidant ascorbyl palmitate (s0a1), and sheared – given the antioxidant ascorbyl palmitate (s1a1).  Heat shock is given by exposing the sheep to the sun. The oxidative stress observed and analyzed was the profile of endogenous antioxidants consisting of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA). The results showed that the combination of shearing and Ascorbyl Palmitate had a significant effect (p<0.05) on the levels of SOD, CAT and GSH-Px in Padjadjaran sheep receiving heat stress.  The conclusion from this study, the shearing treatment and the administration of Ascorbyl palmitate, both independently and in combination, had a beneficial effect on Padjadjaran sheep.